2018
DOI: 10.1002/jbm.b.34154
|View full text |Cite
|
Sign up to set email alerts
|

The effect of osseodensification drilling for endosteal implants with different surface treatments: A study in sheep

Abstract: This study investigated the effects of osseodensification drilling on the stability and osseointegration of machine‐cut and acid‐etched endosteal implants in low‐density bone. Twelve sheep received six implants inserted into the ilium, bilaterally (n = 36 acid‐etched, and n = 36 as‐machined). Individual animals received three implants of each surface, placed via different surgical techniques: (1) subtractive regular‐drilling (R): 2.0 mm pilot, 3.2 and 3.8 mm twist drills); (2) osseodensification clockwise‐dril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 28 publications
2
56
0
4
Order By: Relevance
“…Rather than removing bone particles in the more conventional SD techniques, it has been proposed that an OD drilling sequence will maintain bone by compacting the particles into the osteotomy wall 13,14 . Biomechanical and preclinical studies have indicated significantly higher biomechanical and histomorphometric parameters for OD relative to conventional SD in temporal investigations 14,17–21 . This clinical trial investigated the influence of both surgical instrumentation techniques, SD and OD, on IT and ISQ during the first 6 weeks of healing of implants with different diameters and lengths placed in the anterior and posterior regions of the maxilla and in the mandible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than removing bone particles in the more conventional SD techniques, it has been proposed that an OD drilling sequence will maintain bone by compacting the particles into the osteotomy wall 13,14 . Biomechanical and preclinical studies have indicated significantly higher biomechanical and histomorphometric parameters for OD relative to conventional SD in temporal investigations 14,17–21 . This clinical trial investigated the influence of both surgical instrumentation techniques, SD and OD, on IT and ISQ during the first 6 weeks of healing of implants with different diameters and lengths placed in the anterior and posterior regions of the maxilla and in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving high levels of biomechanical stability have been increasingly required in clinical practice to accommodate the current tendency toward early loading protocols, even for bone types with low density 31,32 . Therefore, the OD instrumentation has demonstrated to improve bone quality as osteotomy size is expanded and guarantee greater levels of physical interlocking at the implant interface, especially in such challenging scenarios 14,17–21 . Histomorphometric analyses of OD in preclinical animal models have exhibited an increased bone mineral density zone of approximately 1 mm circumferentially and apically to the osteotomy wall produced by compacted autograft particles that act as new bone formation nucleating sites, hastening osseointegration 14,17–21 .…”
Section: Discussionmentioning
confidence: 99%
“…The polyurethane sheet simulation provides a highly standardized design model for dental implant and drilling preparation techniques. In fact, several bone substrates have been proposed for in vitro implant studies such as bovine ribs, sheep mandible, pig tibiae and human cadaveric bones; however, local anatomical and density variability, environmental and sample temperature and humidity, as well as biological sample conservation represent potential limitations and determinant factors [5,27,[33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study was designed to verify if the OD technique could be a viable approach for standardization of the healing chamber in low-density bone when using dental implants with a biomimetic surface. The ilium of a sheep was used as the animal model because this region is considered as a low-density bone 18,27,32 , and it was already used in other histomorphometric studies involving dental implants without the need to euthanize the animals 30 . The implants used in this study have a bioactive surface with nanostructured hydroxyapatite and the only difference between the groups was the instrumentation technique of the implantation bed.…”
Section: Discussionmentioning
confidence: 99%